Competitive Advantage of SMEs Through Innovation to Reach International Markets - Ivan Armawan; Imam Mukhlis; Danardana Murwani (HM Publisher, 2023)
This study aims to identify various characteristics related to competitive advantage in SMEs through innovation. This research is a scoping review using PRISMA. The stages in conducting a scoping review that must be carried out are the focus of the review, using the PEO framework (problem, exposure, and outcome), identification of relevant studies, process descriptions, and identification of literature with PRISMA flowcharts, data extraction, and mapping or scoping. The inclusion criteria used in selecting the scoping review study were publication of manuscripts in the last five years (2018-2022), nationally accredited and internationally indexed journals, original articles, and articles in Indonesian or English. The keywords used in the article search were